Ratio of roughage to grain for fattening steer calves - Richardson, D.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
The physical balance or ratio of roughage to concentrates is an important factor to consider in the ration of fattening cattle. Beef cattle serve as one of the principal means of marketing roughage. Since a large amount of roughage is produced in Kansas and throughout the Midwest, it is desirable to have information concerning the maximum amount of roughage that can be used in fattening rations, consistent with maximum and economical production. This experiment was planned to secure information on the effects of different levels of roughage on average daily gain, teed requirement per unit of gain, quality of finish, carcass quality and selling price.
Keywords: Beef; Roughage; Grain; Gain